Acesso à informação pública e transparência ativa : um estudo do sítio institucional da Universidade Federal do Espírito Santo - Oliveira, Andressa Cattafesta de (2017)
Since the start validity of the law no.12.527/2011, also named Lei de Acesso à Informação (LAI), it becomes required in the public sphere, the fulfillment of specific parameters of transparency, relating not only accountable date, but also to general information that reflects the management of public entities and agencies. The brazilian federal universities, due to its lawful nature, have the duty to follow this legislation and therefore Universidade Federal do Espírito Santo (UFES), the only federal university located in capixaba lands, is inset in context. This paper has as a goal the analysis of current exercise of public transparency in UFES, especially the active transparency, from an observation model based on the established by LAI, and its regulations in the Executive Federal Power sphere through the decree no 7.724/2012 and further guidelines by the Federal Government. The methodology of this research presents the nature of applied research, general objectives of exploratory and descriptive characteristics, qualitative approach to the problem, technical bibliographical and documentary procedures and method of deductive approach with transverse temporal cut (cross-sectional), resorting to direct observation performed by web access as data collection instrument. Alternatively, the recommendations published in academic and scientific research, doctrines, external audits, judicial decisions and work carried out by non-governmental organizations (NGOs) and state agencies and entities were verified. This research aims to analyze the current practice of public transparency in UFES, especially active transparency, based on an observation model based on what LAI establishes, its regulation in the sphere of the Federal Executive Branch through Decree No. 7,724 / 2012 And other orientations of the Federal Government. Subsidiarily, consultations were carried out with the other institutional sites of the other Brazilian federal universities and with the recommendations published in academic and scientific research, doctrines, external audits, judicial decisions and work carried out by non-governmental organizations (NGOs) and state bodies and entities. As a result of this paper, a diagnosis of the practice of active transparency by the UFES was obtained, with the aim to improve the active transparency exercised by UFES and therefore the improvement of public management